Prediction of Contact and Lubrication Characteristics of Micro-textured Surface Under Thermal Line Contact EHL - Zhao, Jiang; Li, Zhengminqing; Zhang, Hong; Zhu, Rupeng (Frontiers in Mechanical Engineering, 2021)
In this study, a method combining numerical surface generation technology and three-dimensional hot-line contact EHL is employed to evaluate the contact characteristics of micro-textured surfaces under high-load line contact. Based on numerical simulation, the film thickness, film pressure, friction coefficient and surface flashing temperature of the virtual texture surface with different cross-sectional shapes and sizes are studied. On this basis, the subsurface stress at the contact point is calculated by the DC-FFT algorithm. The results show that, compared with a smooth surface, the micro-textures of different shapes all increase the average oil film thickness of the surface and reduce the friction coefficient, but at the same time lead to an increase in the contact stress of the surface. By changing the width and depth of the texture, the maximum film pressure has changed by 11.4% and 18.5%, respectively.